DISTORSI INTEGRITAS DAN PENCEGAHAN KORUPSI - M. Husein Maruapey (Universitas Islam Islam Sumatera Utara, 2020)
The phenomenon of law enforcement after the revision of the KPK Law which was updated to Law No. 19 of 2019 has drawn a variety of criticisms. Research with the title Distortion of Integrity and Corruption Prevention, with the location of the study at the Faculty of Social Sciences and Communications, Djuanda University, Bogor. In the observation of researchers that the revision of the KPK Law is a distortion causing the weakening of the duties and functions of the KPK in preventing corruption. Proven Case of Substitution of Inter-Time Members of the House of Representatives from the PDIP (HM) faction which is floated makes the public doubt the integrity of this Rasuah institution. Using descriptive analysis methods, researchers hope to describe the object under study through data or samples that have been collected as they are. Data and information obtained are then collected and analyzed using assessment scores based on predetermined criteria for further interpretation in order to obtain maximum results.The results obtained after being analyzed by WMS (Weight Mean Score / (M = Ʃf (x) / n) show Between Integrity and Law Enforcement through the Tiki-Taka Strategy in Corruption Prevention can be quite Good